Social Media and Construction of Beliefs: Perceptions of Youth Regarding Role of Social Networking Sites (SNS) in Creating Gender Stereotypes - Saba Sultana; Batool, Dr. Sumera; Saima Iqbal (Journal of Peace, Development and Communication, 2021)
This research aims to explore the perceptions regarding role of social networking sites (SNS) in construction of beliefs about gender stereotypes by focusing on how gender is perceived among social media users. Further it explores how youth present and project themselves in terms of gender attributes on social networking sites. Current research is exploratory in nature and employed In-depth-interview as research method. The sample comprised of youth selected through purposive sampling procedure. The measures for collecting data encompassed a face sheet including demographic details and interview protocol was also developed. The findings revealed that there are diverse perceptions regarding gender stereotypes among SNS users. Perceptions regarding gender stereotypes and their self-presentations on SNS revealed that men are considered as dominating and authoritative while women are considered as emotional. SNS are constructing and reshaping gender streotypes among users where males present themselves as chraming and poweful whereas female users having beauty craze as a vibrant trait of their personality. Mostly youngsters are busy in their self praise and have become their own role models.